Performance of direct-sown and clonally-propagated transplanted rice (Oryza sativa) under semi-deep-water condition - SHARMA, A R; GHOSH, A (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted at Cuttack (Orissa) during rainy season of 1994 and 1995 under semi-deepwater conditions (0-100 cm) to study the yield performance of'Panidhan' rice (Oryza sativa L.) established by direct seeding and transplanting with either conventional nursery seedlings or tillers uprooted from the direct-sown crop (clonal propagation). Rainfall and nooding patterns varied widely in 2 years, particularly in the early part of the growth season, which caused large variation in the initial establishment and ultimate crop performance. The crop sown in dry soil (18 May 1994) and saturated soil (8 June 1995) with either 400 or 600 seeds/m2 produced significantly higher grain yield (2.52-2.99 tonnes/ha) than the crop transplanted (0.77-1.79 tonnes/ha) during July-August under higher depths of water (35-45 cm). The yield of crop sown with 600 seeds/m2 remained unaffected when clonal tillers @ 70-90/m2 were uprooted at 50 days (in 1994) and 30 days (in 1995) of growth but further delay in the uprooting of tillers up to 90 days (in 1994) and 75 days (in 1995) decreased yield by 0.34-0.85 tonnes/ha compared with the undisturbed crop. The decrease in yield was due to reduced panicle number m2 which was not compensated by increased panicle weight. The transplanted crop raised from clonal tillers performed better (1.07-2.28 tonnes/ha) than that from nursery seedlings (0.46-1.29 tonnes/ha). The clonal tillers were taller (78.3-88.7 cm) and had more dry weight (0.86-2.05 g/plant) which helped in their better establishment and greater survival under the similar flooded environment than the nursery seedlings (66.3-76.3 cm height and 0.5-0.85 glseedling dry weight), which collapsed after transplanting and thus established poorly. Theretore, stand establishment of rice either by direct seeding or transplanting with clonal tillers is beneficial tor improving productivity under semi-deep-water conditions.